Comparison of Undergraduate Religious Education Curriculum in Indonesia and Malaysia - Ismail, Ahmad; Junaedi, Mahfud; Hassan, Zainudin bin; Nasikhin, Nasikhin (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the differences in the undergraduate curriculum of Islamic teacher education in Indonesia and Malaysia. This study is a qualitative type where data were collected through interviews, observations, and document analysis. The study, which took place at UIN Walisongo Semarang, Indonesia, and the University of Technology Malaysia, showed that there are differences in the structure and management of the curriculum of Islamic religious education study programs, namely; 1) In Indonesia, a bachelor's degree in Islamic religious teacher education can only be obtained by attending university immediately after students complete high school. In contrast, in Malaysia, high school graduates are required to follow one of the matriculation, foundation, or diploma programs for two years before continuing their undergraduate education at the university or the Institute of Teacher Education (IPG). 2) To complete a bachelor's degree in Islamic education, Indonesian students must complete 144 credits in a minimum of 3.5 years and a maximum of 7 years, while in Malaysia only 128 credits are required to be completed in a minimum of 4 years and a maximum of 6 years. 3) Although both are supervised by the dean, the curriculum of the Islamic education study program in Indonesia is completely under the control of the chairperson of the study program, while in Malaysia, 40% is designed by the School of Education department (pedagogy area) and 60% is managed by the Tamaddun Academy (professional and social-personality ability area).